Impartial policymakers prefer to impose carbon pricing to capping, especially when combined with offsets - Felix Kölle; Dorothea Kübler; Axel Ockenfels (Ecological Economics, 2024)
Sustainable socio-economic development requires a global reduction of greenhouse gas emissions. We utilize an incentivized experiment to map the preferences of `policymakers' over climate actions of `decision-makers'. Our design guarantees that these preferences are unaffected by selfish motives such as a concern about being re-elected or an unwillingness to pay for the greater good. Few of our impartial policymakers choose interventions that leave the autonomy of decision-makers' completely untouched. The choice patterns of those who intervene suggest that policymakers care not only about minimizing emissions, but also about how emissions are reduced. Policymakers strongly prefer pricing policies over capping emissions, and among the pricing policies, they prefer those that include voluntary carbon offsets, even if this leaves considerable scope for decision-makers to selfishly emit CO2. The reason is that policymakers expect decision-makers to voluntarily offset some of their emissions at their own cost, and believe that this would eventually improve the outcome in terms of both emissions and the decision-makers' profit relative to a standard carbon pricing policy (without offsetting). Our decision-making data confirm this expectation.
Keywords: 330; CO2 Emissions; Carbon Taxes and Offsets; Decision-Making Experiment; Choice Architecture